2-Arachidonoyl glycerol sensitizes the pars distalis and enhances forskolin-stimulated prolactin secretion in Syrian hamsters. (April 2014) - Yasuo, Shinobu; Fischer, Claudia; Bojunga, Joerg; Iigo, Masayuki; Korf, Horst-Werner
<x xml:space="preserve">Abstract</x> 2-Arachidonoyl glycerol (2-AG) is a major endocannabinoid and an important regulator of neuroendocrine system. In Syrian hamster and human, we found that 2-AG is synthesized in the hypophysial pars tuberalis (PT), an interface between photoperiodic melatonin signals and neuroendocrine output pathways. The target of 2-AG produced in the PT is likely to be the pars distalis (PD). Here we demonstrate that 2-AG in combination with forskolin stimulated prolactin secretion from PD organ cultures of Syrian hamsters, whereas incubation with 2-AG alone had no effect. Forskolin-induced prolactin secretion was also significantly enhanced when cultured PD tissue was preincubated with 2-AG. The stimulatory effects of 2-AG on prolactin secretion were blocked by AM251, a selective CB1 antagonist, and were still observed in the presence of quinpirole, a D2-class dopamine receptor agonist. 2-AG also enhanced prolactin secretion in the presence of adenosine, while it had little effect when applied together with adenosine diphosphate (ADP) and adenosine triphosphate (ATP). Moreover, the effect of forskolin was mimicked by adenosine in a dose-dependent manner. In conclusion, our data suggest that 2-AG sensitizes the PD tissue to potentiate the stimulating effects of forskolin and adenosine on prolactin secretion and thus provide novel insight into the mode of action of 2-AG in the PD.